Flash Card Media Development in Grade 1 Indonesian Language Learning at Madrasah Ibtidaiyah Negeri 2 Jember - Husnul Hotimah (Engineering: Journal of Mechatronics and Education, 2024)
This research aims to address the low interest and reading skills of students in Indonesian language lessons by developing flashcard media based on alphabet material. The method used is Research and Development (R&D) with the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The development results in a product in the form of A4-sized flashcards made from 250 gsm art ivory paper, totaling 29 cards, designed using the Canva application.The results of this study show that the validity test yielded very good results, with a validity level of 90% from media experts, 88% from content experts, 98% from teachers, and 73.5% from students. The total validity score is 87.3%, which falls into the very feasible category and does not require revisions, allowing this media to be implemented in learning activities. The developed media flashcards can enhance motivation and are suitable for improving students' understanding in the subject of Indonesian Language. This flashcard can make learning more engaging, interactive, and easier for students to understand the material, thus it is hoped to significantly improve students' learning outcomes.